Unifikasi Kalender Hijriah Internasional dalam Perspektif Yusuf Al-Qaradawi - Abdul Mufid (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2019)
This article focuses on Yusuf al-Qaradawi 's understanding of the Unification of the Hijri Calendar. The unification of the calendar has been constrained by the method used to determine the beginning of the hijri month, reckoning and rukyat. As a result, various Muslims in various regions often experience different months, especially at the beginning and end of the month. The difference in various regions, according to al-Qaradawi, is contrary to the principle of unity and unity which is owned by Muslims throughout the world. Therefore, investigating the idea of ​​unification in al-Qaradawi 's understanding, how the building of his thoughts, the thesis of his argument and its implications for the unification of the Hijri calendar is interesting to do. This research is entirely library research with a historical approach (intellectual history and social history). The method used is social-humanities integration with natural science; astronomy. This research concludes that Yusuf al-Qaradawi 's understanding of rukyat hilal is the hope of al-Qaradawi urgently for the realization of the union of fasting and Muslim holidays in Europe with several reasons including the minority of Muslims there, not the unification of all Muslims in the face of the earth. Al-Qaradawi realized that the unification of Muslims throughout the world was difficult to materialize.